A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 4 PEKANBARU IN USING PREPOSITIONS - Aritonang, Amelya Putri; Supriusman, Supriusman; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study was aimed at describing the ability of the second year students of SMPN 4 Pekanbaru in using prepositions. The population of this study was all of the second year students of SMPN 4 Pekanbaru in the 2018/2019 academic year. The number of sample was 37 students who were chosen by using cluster random sampling technique. The data were collected by administering a test to the students in the form of gap filling type which consisted of 40 items. The result of the data analysis showed that the mean score of the students’ ability in using prepositions is 76.55. It can be concluded that the ability of the second year students of SMPN 4 Pekanbaru in using prepositions was categorized into good level.Key Words : Study, Ability, Prepositions.